2012
DOI: 10.1097/ta.0b013e3182452270
|View full text |Cite
|
Sign up to set email alerts
|

Focus on pediatric intentional trauma

Abstract: An important pattern of intentional injuries can be seen where preventative efforts can be strengthened regardless of urban or rural area: the very young as shaken baby cases and the teens, who unfortunately, accounted for the majority of suicidal attempts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…An increasing trend of VRT and SA was recorded in our series in accordance with international literature (23,30,31), representing the mechanisms associated with the most severe trauma and a higher request for interventions (3,4). We noticed a speed up in the rise of VRT and SA during the C-19 outbreak and its restrictive regulations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An increasing trend of VRT and SA was recorded in our series in accordance with international literature (23,30,31), representing the mechanisms associated with the most severe trauma and a higher request for interventions (3,4). We noticed a speed up in the rise of VRT and SA during the C-19 outbreak and its restrictive regulations.…”
Section: Discussionsupporting
confidence: 88%
“…From the comparison between younger and older than 13 years old PTs, a higher proportion of VRT and SA came up in the older group, with an increasing number over the study period, leading to VRT and SA occurring exclusively in teenagers in 2020 at NTC. The trend of SA among adolescents has been growing for decades (30), representing one of the leading causes of death (23,31). However, we observed a spike in self-in icted trauma in the last year of the study, probably pushed by the quarantine discomfort.…”
Section: Discussionmentioning
confidence: 54%
“…Specifically, studies comparing rural and urban pediatric trauma generally demonstrate higher incidence and mortality in rural areas [ 6 8 ], while data from Canada [ 9 ] suggests non-accidental trauma is more prevalent in urban areas. Non-accidental trauma in the United States is associated with more severe injury and worse outcomes than unintentional injuries [ 4 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] As a consequence, there have been numerous efforts to reduce injuries in the school setting, including increased supervision of physical activities, improving student:teacher ratio, teaching students how to deescalate bullying, adding safety officers, teaching school staff how to address violence, and extra activities for students such as music and arts classes to avoid unstructured or unsupervised time in school. 2,10,22,24 Pediatric intentional and unintentional injuries have been thoroughly discussed in the literature, 20,[25][26][27][28][29][30] and several studies have identified a need for further research to understand intentional school-based injuries. [1][2][3][4][5][6][7]10,24,25,[31][32][33] With the increasing awareness of physical and mental health issues associated with intentional injuries resulting from interpersonal violence and bullying in children, it is important to examine the overall trend for such injuries in the school setting to tailor appropriate measures for safety and prevention.…”
mentioning
confidence: 99%